Statistical Measures for Usage‐Based Linguistics. Issue 1 (June 2015) - Gries, Stefan Th.; Ellis, Nick C.; Norris, John M.; Ross, Steven J.; Schoonen, Rob
<x xml:space="preserve">Abstract</x> The advent of usage‐/exemplar‐based approaches has resulted in a major change in the theoretical landscape of linguistics, but also in the range of methodologies that are brought to bear on the study of language acquisition/learning, structure, and use. In particular, methods from corpus linguistics are now frequently used to study distributional characteristics of linguistics units and what they reveal about cognitive and psycholinguistic processes. This paper surveys a range of psycholinguistic notions that are becoming ever more important in theoretical and cognitive linguistics—for example, frequency, entrenchment, dispersion, contingency, surprisal, Zipfian distributions—and current corpus‐linguistic approaches toward exploring these notions and their roles for linguistic cognition.